The Pragmatists and the Human Logic of Truth - Claudine Tiercelin (Collège de France, 2014)
The expression "human logic of truth" is Frank P. Ramsey's:"Let us therefore try to get an idea of a human logic which shall not attempt to be reducible to formal logic. Logic, we may agree, is concerned not with what men actually believe, but what they ought to believe, or what it would be reasonable to believe. What then, we must ask, is meant by saying that it is reasonable for a man to have such and such a degree of belief in a proposition?" Many themes developed by Ramsey in his work (o...